Dynamic Monitoring and Assessment of Vegetation Cover in Mining Areas Based on Remote Sensing Technology - Ma, Wei; Xu, Changjing (Transactions on Environment, Energy and Earth Sciences, 2024)
Mining activities often damage natural ecosystems, leading to soil erosion, vegetation destruction, and a decline in biodiversity. Monitoring and evaluating ecological restoration is crucial to address these environmental issues and restore ecological balance effectively. The application of remote sensing technology in the ecological restoration of mining areas is of great significance. This study focuses on the subsidence area of the Xishan coalfield in Shanxi Province, using remote sensing data from the Landsat series of satellites to assess the progress of vegetation restoration. The study indicates that from the beginning of the restoration in 2007 to 2021, the vegetation growth in the Xishan coalfield subsidence area has significantly improved, with the area of restored vegetation gradually increasing. Since the implementation of the ecological restoration plan by the city of Taiyuan in 2008, the vegetation coverage in the mining area has increased yearly, especially after 2010, with a noticeable acceleration in the restoration speed. The vegetation restoration in the Xishan coalfield subsidence area has significantly increased within the main subsidence area and extended to the surrounding regions. However, the expansion of Taiyuan has somewhat impacted vegetation coverage in certain areas. This study emphasizes the importance of remote sensing technology in ecological restoration and provides data support for continuously monitoring and assessing the ecological environment in mining areas.